Hidrogel contendo (1->6)-ß-d-glucana (lasiodiplodana): desenvolvimento, caracterização e avaliação da atividade cicatrizante - Nissola, Candida (2019)
β-Glucans have attracted the interest of researchers and industries in the pharmaceutical and cosmetic sectors due to its biotechnological and functional properties. Among the β-glucans, lasiodiplodan (LAS) an exopolysaccharide (EPS) of the type (1→6)-β-D-glucan produced by the ascomycete Lasiodiplodia theobromae MMPI and recently described in scientific literature, has demonstrated different biological potentialities. The present study aimed to develop, characterize and evaluate the healing stimulant potential of a lasiodiplodan-containing hydrogel (0.5%). The developed formulation was evaluated for physicochemical (color, odor, pH, spreadability, viscosity, water activity and moisture) and microbiological parameters (research of mesophilic bacteria, Staphylococcus aureus, Pseudomonas aeruginosa, Coliform at 35 and 45 ° C and total mold and yeast count) and preliminary stability tests. The antioxidant potential of the formulation was evaluated for its ability to scavenge DPPH and hydroxyl (OH•) radicals and ferric reducing power (FRAP). Histological analysis of cutaneous tissue from the dorsal region (Wistar rats) subjected to excisions was performed. After 4, 7, 10 and 14 days, the experimental animals were euthanized and the skin wounds were evaluated for macroscopic appearance and histological analysis. At the end of each analysis period, re-epithelialization, cell proliferation and collagen production were evaluated. The hydrogel containing LAS demonstrated physicochemical stability, microbiological quality and antioxidant potential, especially in relation to its ability to scavenge hydroxyl radicals. The LAScontaining hydrogel stimulated cell re-epithelialization and proliferation on all treatment days compared to the control hydrogel (without LAS). The hydrogel stimulated an increase of collagen fibers, with significant difference of type I collagen fibers on days 7, 10 and 14 and type III on the seventh and tenth day. Lasiodiplodan (1→6)-β-Dglucan showed immunomodulatory activity in wound healing and the hydrogel containing this macromolecule may be an alternative in wound care.